Financial remedy outcomes on divorce in England and Wales: Not a 'meal ticket for life' - Miles, JK; Hitchings, Emma (LexisNexis Australia, 2018)
This paper reports data from a recent mixed-methods study of financial settlement on divorce in England & Wales. It aims to contribute to current debates about the prevalence of, and justification for, orders for spousal support (maintenance/periodical payments) following divorce. A central finding from the court file data examined in this study is how spousal support (paid almost exclusively by husbands to wives) is very largely confined to cases involving minor dependent children. The paper situates the discussion of cases that proceed through the legal system (only a minority of all divorces) in the wider context of general population data that show continuing economic disadvantage for women following divorce, largely as a result of their child care responsibilities. It concludes with a plea that discussion of reform in this area be underpinned by a firm grounding in the best available empirical data about the realities of financial provision on divorce, which are not to be found in media-reporting of high-profile, predominantly ‘big money’ cases.